Two-rope method for dissecting esophagus in McKeown MIE - Wang, Qian; Liu, Huibing; Zhang, Luchang; Jin, Defeng; Cui, Zhaoqing; Cai, Rongqiang; Huang, Junjun; Wei, Yutao (Frontiers in Surgery, 2023)
Objective Minimally invasive McKeown esophagectomy (McKeown MIE) is performed at many hospitals in esophageal cancer(EC) treatment. However, secure and quick methods for dissecting the esophagus and dissecting lymph nodes in this surgery are lacking. This study introduces a simple, secure and feasible esophagus dissecting technique named two-rope method. Two mobile traction ropes are placed around the esophagus and we tow these ropes to free the esophagus, dissect the lymph nodes, and decrease the operative trauma. Materials and Methods Retrospective analysis was performed on 112 patients who underwent McKeown MIE in our center from January 2019 to September 2021. They were assigned into two groups based on the method of dissecting the esophagus: Group A (two-rope method, 45 cases) and Group B (regular method, 67 cases). Operation time, thoracic operation time, the number of dissected thoracic lymph nodes, and postoperative complications were compared between the two groups after propensity score matching. Results Using 1:1 nearest neighbor matching, we successfully matched 41 pairs of patients. Operation time, thoracic operation time, and the duration (ac to as) was significantly shorter and the size of the abdominal incision was significantly smaller in the Group A than Group B (p < 0.05). There was no statistically significant difference in the number of dissected thoracic lymph nodes, pulmonary infection, anastomotic leak, recurrent laryngeal (RLN) injury, and chylothorax between the two groups (p > 0.05). Conclusions Two-rope method to free the esophagus and dissect thoracic lymph nodes in McKeown MIE has significant advantages compared with the regular method. The technique is, therefore suitable for widespread adoption by surgeons.